Archeological Survey in Northeastern Death Valley National Monument - Barton, C. Micheal (the Digital Archaeological Record)
This report describes the results of an archeological clearance survey along 61 km of the northern and northeastern boundaries of Death Valley National Monument. The purpose of this survey was to identify cultural resources within a right-of-way for a fence, planned for this part of the monument boundary, in order the assess the impact of fence constructi on on these resources. Bri ef di scussi ons of the present and past environment and the cultural history of the survey area are presented as background. A description of survey methods is followed by a detailed discussion of the cultural material found. Eleven sites were identified, including eight prehistoric and three historic sites. Of the prehistoric sites, four are low-density lithic scatters on the surface, lacking diagnostic artifacts. The remaining prehistoric sites include a small sherd and lithic scatter, two rockshelters, and a large (probable) base camp. Ceramics found at three of these latter sites date them to the Shoshonean period (A.D. l200-contact). The three historic sites are a small site of uncertain function, a small mining camp, and a very large site that probably represents the historic town of Amargosa. Isolated finds include 48 prehistoric and historic artifacts (including a possible petroglyph), 28 rock clusters or cairns, and two mines. The description of the cultural materials is followed by an interpretative discussion of the nature and distribution of these materials. Finally, the archeological significance and potential impact of fence construction on the identified cultural resources is assessed, and cultural resource management recommendations are presented.